Factors that influence ethical judgement of Kota Bharu Municipal Council officials / Rabaatul Azira Hassan - Hassan, Rabaatul Azira (2021)
Rampant unethical incidences have been reported in public sectors and municipal councils are not spared from these predicaments. Many indicate that these incidences are due to the involvement of municipal officials in unethical incidences such as abuse of power, breach of duties and manipulation of financial transactions. The incidences have eroded the public trust towards municipal officials. They accuse that the officials are unethical in their actions, and eager in enriching themselves instead of protecting the interest of the public. Indeed, unethical actions are derived from unethical judgments which are influenced by various factors. Applying Hunt and Vitell theory, the objectives of this study is to examine the ethical judgments in relation to organizational ethical climate, deontological evaluations of rules compliance and teleological evaluations of perceive consequences. Data were collected from 141 officials of Kota Bharu municipal council and analysed using SPSS statistics version 27. As hypothesized, the findings supported that organizational ethical climate, deontological evaluations and teleological evaluations have significant impact on ethical judgements. This study provides beneficial insights to the government, policy and lawmakers, municipal councils, and academicians that rule compliance (deontology), able to quantify the right over the wrong consequences (teleology) since having a sound organizational ethical climate is vital in the formation of ethical judgments. Hence, it is hoped that enhancing ethical judgements among the officials would regain the public trust towards the municipal council and thus align to the country’s aspiration of becoming a corrupt free nation in due time.